Apocalypse and utopia in the salvagepunk metropolis. Issue 1 (4th March 2023) - Wilson, Japhy
Abstract : This paper explores the nature of utopia in the context of our apocalyptic present. Drawing on Evan Calder Williams' concepts of salvagepunk, it interprets the city of Iquitos in the Peruvian Amazon as a (post)apocalyptic metropolis. It excavates the origins of Iquitos in genocidal violence and extractivist destruction, deconstructs the modernising megaprojects designed to rescue the city from its isolated status, and explores the subaltern forms of its everyday production. In doing so, the paper problematises accelerationist and pluriversal fantasies of escape from planetary socioecological breakdown, and discerns an apocalyptic utopia emerging at the urban cutting edge of the Anthropocene.